Public management and sustainable development in Nigeria : military-bureaucracy relationship - Dibie, Robert A. (Aldershot, Hampshire, England ; Burlington, VT : Ashgate, 2003)
This book examines public management and the trend of sustainable development in Nigeria from 1966 to 1999. It analyzes the trend of change that occurred in Nigeria during the several military regimes and the short democratic government.
Includes index.
Includes bibliographical references: p. (369-396).
osc 06/09/16
Loan
Keywords: Sustainable development; Public administration; Military government; Federal government; Nigeria